Effects of MACPF/CDC proteins on lipid membranes - Gilbert, R; Mikelj, M; Dalla Serra, M; Froelich, C; Anderluh, G (2013)
Recent work on the MACPF/CDC superfamily of pore-forming proteins has focused on the structural analysis of monomers and pore-forming oligomeric complexes. We set the family of proteins in context and highlight aspects of their function which the direct and exclusive equation of oligomers with pores fails to explain. Starting with a description of the distribution of MACPF/CDC proteins across the domains of life, we proceed to show how their evolutionary relationships can be understood on the basis of their structural homology and re-evaluate models for pore formation by perforin, in particular. We furthermore highlight data showing the role of incomplete oligomeric rings (arcs) in pore formation and how this can explain small pores generated by oligomers of proteins belonging to the family. We set this in the context of cell biological and biophysical data on the proteins' function and discuss how this helps in the development of an understanding of how they act in processes such as apicomplexan parasites gliding through cells and exiting from cells. © 2012 Springer Basel AG.